Persistent Left Superior Vena Cava and Partial Anomalous Pulmonary Venous Return in an Old Asymptomatic Female Patient. (19th October 2009) - Sahin, Tayfun; Kilic, Teoman; Celikyurt, Umut; Bildirici, Ulas; Ural, Dilek
Abstract : Persistent left superior vena cava is a rare congenital venous anomaly. It results from failure of closure of the left anterior cardinal vein during cardiac development. It is usually asymptomatic but can be associated with other congenital cardiac defects including atrial septal defects, ventricular septal defects, endocardial cushion defects, tetralogy of Fallot and rhythm disturbances. PLSVC should be considered in the presence of a dilated coronary sinus on transthoracic echocardiography. The diagnosis can be made when injection of contrast in left antecubital vein results in enhancement of the dilated coronary sinus before right atrium. MRI, CT-scan and catheterisation can be used to confirm the diagnosis.